2018
DOI: 10.1136/bmjopen-2018-021512
|View full text |Cite
|
Sign up to set email alerts
|

Determining the pneumococcal conjugate vaccine coverage required for indirect protection against vaccine-type pneumococcal carriage in low and middle-income countries: a protocol for a prospective observational study

Abstract: IntroductionPneumococcal conjugate vaccines (PCVs) prevent disease through both direct protection of vaccinated individuals and indirect protection of unvaccinated individuals by reducing nasopharyngeal (NP) carriage and transmission of vaccine-type (VT) pneumococci. While the indirect effects of PCV vaccination are well described, the PCV coverage required to achieve the indirect effects is unknown. We will investigate the relationship between PCV coverage and VT carriage among undervaccinated children using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 40 publications
(33 reference statements)
1
29
0
Order By: Relevance
“…The degree of indirect effects is likely to be associated with the coverage achieved. 31 The results of this study are consistent with a systematic review that found that carriage of vaccine serotypes declined in non-target age groups after PCV introduction. 11 Reductions in vaccine-type carriage occurred contemporaneously with reductions in vaccine-type invasive pneumococcal disease, supporting the usefulness of carriage as an alternative for disease surveillance to show the population effects of PCV.…”
Section: Discussionsupporting
confidence: 90%
“…The degree of indirect effects is likely to be associated with the coverage achieved. 31 The results of this study are consistent with a systematic review that found that carriage of vaccine serotypes declined in non-target age groups after PCV introduction. 11 Reductions in vaccine-type carriage occurred contemporaneously with reductions in vaccine-type invasive pneumococcal disease, supporting the usefulness of carriage as an alternative for disease surveillance to show the population effects of PCV.…”
Section: Discussionsupporting
confidence: 90%
“…This analysis was part of a multi-site study across the Asia-Pacific region examining the relationship between PCV13 coverage and indirect effects in Lao PDR, Mongolia and Papua New Guinea. 9 The Lao PDR component was embedded within a prospective hospital-based study of the aetiology of ARI. 23 We used the same terminology outlined by Halloran et al in which indirect effects are defined as the population-level effects of a vaccination strategy experienced by individuals regardless of vaccination status.…”
Section: Methodsmentioning
confidence: 99%
“…Community or herd immunity is an important consideration when estimating the full public health value of immunization. The threshold to achieve such community protection can be as high as 95% for measles, but as low as 80% for rubella, and 60% in high-income settings for the effect to begin for pneumococcal vaccination, which means that the programme strength required to derive additional impact varies substantially by vaccine [11][12][13] . These differences in the required critical vaccination coverage rates are due to the basic reproductive ratio of an infection (R 0 ) 14 , which can vary greatly among various infectious diseases.…”
Section: Reviewmentioning
confidence: 99%